تأثير ابتكار المنتج على ولاء المستهلك للعلامة التجارية "دراسة ميدانية على مستهلكي منتجات الأجهزة الخلوية في الساحل السوري" - نصور ريزان; سلوم علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research aims to study the effect product innovation on brand loyalty, a questionnaire was conducted on a convenient sample of the studied mobiles products consumers, and 414 questionnaires were valid. The results indicate that product innovation strategy affects positively brand loyalty, and the most influencing dimension of product innovation strategy on brand loyalty is innovation in mobile style. The researcher recommended the importance of product innovation as an important step in meeting consumer needs and carrying out complementary studies on product innovation. هدف البحث إلى دراسة تأثير ابتكار المنتج على ولاء المستهلك للعلامة التجارية، وتم توزيع استبيانات على عينة ميسرة من مستهلكي منتجات الأجهزة الخلوية محل الدراسة وتم استرداد 414 استبيان صالح للدراسة، وتوصل البحث إلى وجود تأثيراً إيجابياً لاستراتيجية ابتكار المنتج على ولاء المستهلك للعلامة التجارية وأهم بعد لاستراتيجية ابتكار المنتج في التأثير على الولاء للعلامة التجارية هو الابتكار في شكل الجهاز الخلوي، وأوصى الباحث بالاهتمام بابتكار المنتج كاستراتيجية مهمة في تلبية حاجات المستهلك وإجراء دراسات مكملة تتناول ابتكار المنتج.